SOA Distributed Bundles with QoS-aware - Sutheera Puntheeranurak; Aekkawit Chanpen (My University, 2013)
Service replication is leveraged in a Service-Oriented Architecture (SOA) system for distributing services to different servers.It prevents the system from bottle neck and overload problem to improve the availability and reliability of the system.For this work, we focus on dynamic replication that needs an intelligent agent to control the replication procedure.It doesn't only improve the availability and reliability of the system, but it also optimizes resource usage on each server.In this paper, we discuss and propose the QoS-aware platform that aims to monitor the quality of services and decide to start the distributing function service.It makes the replica is deployed properly when a system's load is exceeded the capability of system service.
Keywords: Replication; Service-Oriented Architecture and Web Services